Leukocyte adhesion deficiency II syndrome, a generalized defect in fucose metabolism. - Marquardt, T; Brune, T; Lühn, K; Zimmer, K; Körner, C; Fabritz, L; van der Werft, N; Vormoor, J; Freeze, H; Louwen, F; Biermann, B; Harms, E; et al. (1999)
Leukocyte adhesion deficiency II has been described in only 2 patients; herein we report extensive investigation of another patient. The physical stigmata were detected during prenatal ultrasonographic investigation. Sialyl-Lewis X (sLex) was absent from the surface of polymorphonuclear neutrophils, and cell binding to E- and P-selectin was severely impaired, causing an immunodeficiency. The elevation of peripheral neutrophil counts occurred within several days after birth. A severe hypofucosylation of glycoconjugates bearing fucose in different glycosidic links was present in all cell types investigated, demonstrating that leukocyte adhesion deficiency II is not only a disorder of leukocytes but a generalized inherited metabolic disease affecting the metabolism of fucose.